EVALUASI PENGARUH PUPUK KANDANG AYAM DAN KOMPOS GULMA KI PAHIT (Tithonia Diversifolia) TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max L). - Sajar, Suryani (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
Increasing the production of soybeans is an effort to meet the needs of soybeans. Fertilization is a way to increase the production of soybean plants. The condition of scarcity of inorganic fertilizers makes farmers have to look for other alternatives so that fertilizers are available through the use of available organic waste in the environment, namely chicken manure and kipahit weeds. This study was to evaluate the effect of chicken manure and kipahit weed compost on the growth and production of soybean plants. The 2 factorial randomized block design with factor I varying the dose of chicken manure consisted of T0 (0 tons/ha), T1 (5 tons/ha), T2 (10 tons/ha), T3 (15 tons/ha). Factor II, kipahit weed compost A0 (0 tons/ha), A1 (5 tons/ha), A2 (10 tons/ha) and A3 (15 tons/ha). Real responses were shown in the parameters of plant height, stem diameter, dry weight of shoots and roots, number of productive branches, dry weight of seeds and 100 seeds due to liquid organic fertilizer from tofu water waste. Giving kipahit compost showed no significant response to all treatments. The interaction of liquid organic fertilizer from tofu waste water and chicken egg shell flour did not show a real response to the growth and production of soybean plants. keywords: pupuk, kandang ayam, kompos, kipahit, kedela